2015
DOI: 10.1007/s10973-015-4462-y
|View full text |Cite
|
Sign up to set email alerts
|

Structure characterization of terazosin drug using mass spectrometry and thermal analyses techniques in comparison with semi-empirical molecular orbital (MO) calculations

Abstract: Terazosin (C 19 H 25 N 5 O 4 , MW = 387) drug is a selective alpha 1 antagonist. It is used for lowering the blood pressure. Also, it used for treatment of symptoms of an enlarged prostate and is therefore a drug of choice for men with hypertension and prostate enlargement. In the present study, mass spectrometry (MS) and thermal analyses (TA) were used to investigate the fragmentation decomposition pathways of terazosin and confirmed by semi-empirical molecular orbital (MO) calculation, using PM3 procedure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The transitions correspond to the octahedral geometry of the complex which is also supported by its magnetic susceptibility value (3.06 BM) [25,26,27,28].…”
Section: Magnetic Susceptibility and Electronic Spectral Studiesmentioning
confidence: 55%
“…The transitions correspond to the octahedral geometry of the complex which is also supported by its magnetic susceptibility value (3.06 BM) [25,26,27,28].…”
Section: Magnetic Susceptibility and Electronic Spectral Studiesmentioning
confidence: 55%
“…From Table 4, the values of the recovery and the low values of SD of the proposed methods indicate the high accuracy and precision of the proposed methods for the microdetermination of TRZ, DOX and PIOG drugs in the pharmaceutical dosage forms. The accuracy and the precision of the proposed methods are compared with those obtained from the official methods by student's t-test and F-test, respectively, at confidence limit 95% and P=0.05 [29]. The obtained values of F-test and t-test indicate that there is no significant difference between the accuracy and the precision of the proposed and the official methods and hence the reliability of the proposed methods for the routine analysis of TRZ, DOX and PIOG drugs in pure and in their pharmaceutical formulations.…”
Section: Application Of the Applied Procedures In Comparison With Thementioning
confidence: 99%
“…There are many drugs on the market used for the treatment of various kinds of human diseases, such as Terazosin , Gefitinib , Erlotinib and Lapatinib . Of which, Terazosin is not only used to treat symptoms of an enlarged prostate but also used for men with hypertension and prostate enlargement . In addition, imidazo[1,2‐ c ]quinazoline is a fused tricyclic heterocycle; it is reported that its derivatives have many pharmacological and biological applications including cytotoxic , antimalarial , antimicrobial , and antiapoptotic activities .…”
Section: Introductionmentioning
confidence: 99%